2022
DOI: 10.1038/s41598-022-16209-z
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of trimethylolpropane triester (bio-lubricant) from camelina oil

Abstract: Vegetable oils, whose hydrocarbon structure is very similar to that of petroleum products, are ideal renewable and sustainable alternatives to petroleum lubricants. Bio-lubricants are commonly synthesized by modifying the chemical structure of vegetable oils. In this study, microwave irradiation was applied to intensify the mass-transfer-limited transesterification reaction to produce trimethylolpropane triester (bio-lubricant) from camelina oil as a promising local energy crop. A rotatable RSM-BBD method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Numerous alkali group 1 materials such as KOH, NaOH, NaOCH3, which are dissolved in alcohol and can be applied for microwave-assisted biodiesel synthesis . Under bombardment of electromagnetic power from microwaves, due to the higher dielectric characteristics, alcohol quickly heated to reach the boiling point and provide sufficient energy to initiate the transesterification reaction (Rokni et al, 2022). A study performed a microwave-assisted biodiesel synthesis using papaya oil found nearly 99% biodiesel conversion (Nayak and Vyas, 2019).…”
Section: Microwave-assisted Biodiesel Synthesismentioning
confidence: 99%
“…Numerous alkali group 1 materials such as KOH, NaOH, NaOCH3, which are dissolved in alcohol and can be applied for microwave-assisted biodiesel synthesis . Under bombardment of electromagnetic power from microwaves, due to the higher dielectric characteristics, alcohol quickly heated to reach the boiling point and provide sufficient energy to initiate the transesterification reaction (Rokni et al, 2022). A study performed a microwave-assisted biodiesel synthesis using papaya oil found nearly 99% biodiesel conversion (Nayak and Vyas, 2019).…”
Section: Microwave-assisted Biodiesel Synthesismentioning
confidence: 99%
“…The conversion of triglyceride to esters can be followed or preceded by one or more transesterification reactions to improve production, such as hydrogenation and epoxidation (Cecilia et al, 2020). Different natural oils were used as raw materials to develop sustainable biodiesel and biolubricant as an alternative to fossil fuels (Panchal et al, 2017;Carlucci et al, 2019;Sharma and Sachan, 2019;Djomdi et al, 2020;Encinar et al, 2020;Gul et al, 2020;Ge et al, 2022;Rokni et al, 2022;Shahabuddin et al, 2022;Ulanova et al, 2022;Unruean et al, 2022). The conversion of triglycerides of Vegetable oil into biodiesel is through a transesterification process.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the chemical reaction of TMP triesters synthesized from camelina oil, irradiation was applied via microwave. The optimal settings for independent factors were 1.4%wt catalyst concentration, 1: 3.5 M ratio, and 67.8 min reaction time (Rokni et al, 2022). Cottonseed oil has a composition of oleic (19.4%), linoleic (53.2%), linolenic (0.5%), and palmitic (23.7%) (Djomdi et al, 2020), depending upon the harvesting conditions and consequently, affects the characteristics of resulting bio lubricant after transesterification.…”
Section: Introductionmentioning
confidence: 99%